On Intrinsic Safety of Soft Robots - Abidi, Haider; Cianchetti, Matteo (Frontiers in Robotics and AI, 2017)
The rapidly growing field of soft robotics owes its success to the vast vistas of possibilities they promise. They may be utilized as standalone systems, or work in harmony with the existing robotic technologies. Being based on soft and/or flexible materials, soft robots have usually high dexterity and at the same time, they are also often considered ‘intrinsically safe’. This is generally true and soft-bodied robots can be considered safer from a mechanical point of view, but this is sometimes improperly used. The identification of possible safety loopholes in soft robots is the subject of this paper. After a general overview of safety in robotics, we reported an overview of the main sources of unsafe conditions that may arise by the use of soft robotics technologies. Safety aspects are discussed in three categories quasi-static, dynamic and material failure. Some safety factors exclusive to soft robots such as whiplash like effect and energy stored in highly strained elements are also introduced. Measures to avoid such unsafe conditions are presented such as establishing operational limits and introduction of inspection regimes and arrest systems.